Deposit Insurance and Banking Reform in Russia - Camara, Modibo K.; Montes-Negret, Fernando (World Bank, Washington, DC, 2012)
The objective of this paper is not to review the pros and cons of deposit insurance systems, but to focus, rather narrowly, on the recent adoption of a deposit insurance system (DIS) in Russia, the rationale offered, and the potential impact it might have on the stability and development of the Russian banking system. An attempt is made to draw some lessons from the implementation experience in Russia. The paper starts with a brief description of the Russian DIS, followed by an overview of the banking system's structure and some observations on the sequencing followed for adopting the DIS and the political economy of its adoption. It concludes with a discussion of areas requiring attention.